Three-dimensional printing with waste high-density polyethylene - Gudadhe, Aniket; Bachhar, Nirmalya; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2019)
Fused filament fabrication (FFF) three-dimensional (3D) printing of semicrystalline polymers such as high density polyethylene (HDPE) is challenging because crystallization-induced shrinkage of the filament, as it cools, results in stresses that warp the printed part and debond it from the print substrate. Here, we demonstrate that waste-derived HDPE can be successfully 3D printed by (i) blending with a small fraction (<0.5% by weight) of dimethyl dibenzylidene sorbitol (DMDBS) and (similar to 10%) linear low density polyethylene (LLDPE) and (ii) printing the object with a thin ``brim'' around it that is adhered to the print substrate using common polyvinyl acetate-based glue. We match our experimental results with FEM simulations that provide insight into the origin of the stresses developed during printing. Because HDPE forms a significant fraction of the plastic waste stream, conversion of waste-derived HDPE to 3D printing filament has important technological implications.
Keywords: 3d printing polyethylene printing; polymer blend; Recyclability; warpage

3D printing of semicrystalline polypropylene: towards eliminating warpage of printed objects - Bachhar, Nirmalya; Gudadhe, Aniket; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (Bulletin of Materials Science, 2020)
Fused filament fabrication (FFF) is an extrusion-based 3D printing technique for thermoplastic polymers. In this technique, molten polymer is extruded through a print nozzle and is laid down layer by layer to build up the printed object. Currently, FFF is used primarily to print amorphous or low-crystallinity polymers, such as acrylonitrile butadiene styrene copolymer (ABS) or polylactic acid (PLA). Printing of semicrystalline polymers, such as polyethylene or polypropylene remains particularly challenging. During FFF of semicrystalline polymers, large thermomechanical stresses are generated when the polymer solidifies on cooling. These stresses result in warpage of the printed part. Here, we analyse the factors that influence stresses generated during FFF 3D printing of a commercial semicrystalline polymer, isotactic polypropylene. We investigate the effect of height of the printed object on part warpage, as well the effect of infilling during printing. We demonstrate that the stresses generated during FFF can be substantially decreased by incorporation of a `brim', viz. a thin layer at the base of the printed object, and by adhering the brim to the print substrate using common polyvinyl acetate-based glue. We systematically investigate the effect of the brim size on the warpage of the printed object. We support our experimental findings with finite element method (FEM) simulations that explain the mechanism of stress buildup during printing. The trend in stresses calculated in the FEM simulations parallel the warpage measured in the experiments. Thus, this work represents an important methodological advance towards warpage-free FFF printing of semicrystalline polymers.
Keywords: 3D printing; polypropylene printing; warpage

Upcycling of postconsumer recyclate polypropylene into low warping and high toughness 3D printable filaments - Gopal, Animesh; Patil, Prashant; Pol, Harshawardhan; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2025)
Polypropylene (PP) is widely used in commodity applications owing to its chemical stability, mechanical properties and low cost. However, almost 50% of the produced PP ends up as postconsumer waste (PCW) within a short period of usage. Being a non-biodegradable polymer, recycling PCW PP is important to mitigate plastic waste in landfills. Nonetheless, recycling or upcycling postconsumer recyclate (PCR) PP into valuable resources without deterioration in physical and mechanical properties is a challenge. This report presents an approach to upcycle PCR polypropylene (rPP) into high quality 3D printing filament that not only prints with very low warpage but with significantly high elongation at break and toughness. Incorporation of poly(butylene adipate-co-terephthalate) (PBAT) along with maleic anhydride grafted polypropylene (MAPP) in specific proportions led to a significant enhancement in mechanical properties, miscibility, crystallization behavior, and 3D printability. rPP/PBAT blends with 20 wt % PBAT and 10 wt % MAPP exhibited a 62-fold enhancement in elongation at break over rPP (from 1.88 to 118.29%) and a 72-fold increase in toughness (from 2 to 143.60 kJ/m3) with almost similar tensile strength. The final printed components had better layer adhesion and structural stability with a dramatic decrease in warpage, from 25.82% for pristine rPP to only 7.86% for rPP/PBAT blend. Isothermal crystallization studies and data analysis using the Avrami equation showed that crystallization half-time (t 1/2), which measures the duration needed for half of the total crystallinity to form, increased from 12.6 s for rPP to 66 s for the rPP/PBAT blend. This report demonstrates an approach to upcycle PCR PP, a positive step toward realizing the goals of circular economy and sustainable additive manufacturing.
Keywords: Crystallization; FFF 3D printing; polypropylene/poly(butylene adipate-co-terephthalate)blends; toughness; warpage

Low warping and high toughness recycled high density polyethylene for fused filament fabrication 3D printing - Gopal, Animesh; Chaubal, Aman; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2026)
The incorporation of recycled polymers in additive manufacturing offers a sustainable pathway to reduce plastic waste while enabling cost-effective production of functional components. High-density polyethylene (HDPE) is an attractive material for 3D printing owing to its low density, chemical resistance, and recyclability. However, its high crystallinity and tendency to shrink often lead to warpage and poor interlayer adhesion. This study proposes a blend-based strategy to overcome these limitations by incorporating tough linear low-density polyethylene (LLDPE) into recycled HDPE (rHDPE). The blends were prepared through melt extrusion, and their mechanical, rheological, morphological, and thermal properties, and 3D printability were comprehensively evaluated. rHDPE/LLDPE blends showed a remarkable improvement in elongation at break (from 3.2% to 84.7%) and toughness without compromising tensile strength. Addition of LLDPE led to a moderate reduction in the crystallinity of rHDPE/LLDPE blends (from 69% to 52.5%) but a significant reduction in the warpage of 3D printed samples (from 27% to 7.6%). Rheological and morphological analyses confirmed good miscibility and uniform phase distribution in the blends, with increasing LLDPE content enhancing complex viscosity and melt elasticity. Overall, the rHDPE/LLDPE blends exhibit superior mechanical performance and reduced warpage, establishing their potential for FFF 3D printing applications.
Keywords: Crystallization; FFF 3D printing; high-density polyethylene blends; Recycling; toughness; warpage